2015
DOI: 10.18632/oncotarget.4667
|View full text |Cite
|
Sign up to set email alerts
|

ZIP4 silencing improves bone loss in pancreatic cancer

Abstract: Metabolic bone disorders are associated with several types of human cancers. Pancreatic cancer patients usually suffer from severe nutrition deficiency, muscle wasting, and loss of bone mass. We have previously found that silencing of a zinc transporter ZIP4 prolongs the survival and reduces the severity of the cachexia in vivo. However, the role of ZIP4 in the pancreatic cancer related bone loss remains unknown. In this study we investigated the effect of ZIP4 knockdown on the bone structure, composition and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Indeed, it was recently reported that animals bearing the Lewis Lung carcinoma present muscle wasting associated with decreased BMD, although alterations of bone strength were not taken into consideration (Choi et al, 2013). Similarly, bone tissue and bone strength were significantly affected in murine models of pancreatic cancer (Greco et al, 2015; Zhang et al, 2015). In the present study, we showed that regardless of the type of tumor, muscle and fat loss were generally accompanied by significantly decreased BMD, while BMC was reduced exclusively in the Apc Min/+ animals (Figure 5).…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, it was recently reported that animals bearing the Lewis Lung carcinoma present muscle wasting associated with decreased BMD, although alterations of bone strength were not taken into consideration (Choi et al, 2013). Similarly, bone tissue and bone strength were significantly affected in murine models of pancreatic cancer (Greco et al, 2015; Zhang et al, 2015). In the present study, we showed that regardless of the type of tumor, muscle and fat loss were generally accompanied by significantly decreased BMD, while BMC was reduced exclusively in the Apc Min/+ animals (Figure 5).…”
Section: Discussionmentioning
confidence: 98%
“…Raman bands from proline and amides (I and III), respectively, represent the contribution from collagen and the organic matrix (including collagen and noncollagenous proteins). Spectral parameters for composition analysis were determined as: collagen mineralization as indicated by mineral‐to‐collagen ratio (phosphate ν1/proline) and mineral‐to‐matrix ratio (phosphate ν2/amide III); mineral crystallinity: reciprocal of the full‐width at half‐maximum of phosphate ν1 (100×); carbonate‐to‐collagen ratio: carbonate/proline; and relative collagen content indicated by collagen‐to‐matrix ratio (proline/amide I or III) …”
Section: Methodsmentioning
confidence: 99%
“…Exosomal ZIP4 is associated with cancer growth and can be utilized as a diagnostic biomarker for pancreatic cancer 19 . Furthermore, silencing of ZIP4 attenuates bone loss in pancreatic cancer patients 20 . In addition, as a novel determinant of tumor invasion, ZIP4 contributes to tumor recurrence after liver transplantation in patients with hepatocellular carcinoma (HCC) 21 .…”
Section: Introductionmentioning
confidence: 99%